Estudo da imobilização das enzimas neutrase e L-arabinose isomerase em suportes de baixo custo - Chinelate, Gerlla Castello Branco (2013)
For reasons of the need to improve studies of enzyme immobilization Neutrase and L-arabinose isomerase, the present study aimed to evaluate the potential of materials like cashew apple bagasse (CAB), coconut shell fiber (FCV) and chitosan (QUIT) as supports natural and with low cost. Neutrase for the three media studied underwent chemical treatments and activation with glycidol, epichlorohydrin and glutaraldehyde. The immobilized Neutrase counted on the enzyme concentration offered to all substrates was 8.8 U/mL (51 mg proteína.g ) at 25°C for 3 hours. The activities of soluble and immobilized Neutrase were evaluated by spectrophotometric analysis at 700 nm according to the TCA-Lowry assay. The derivatives were analyzed for yield of immobilization (RI), activity recovered (ARec), half-life (t1/z) and thermal stabilization factor (SF) of 60°C, compared with the soluble enzyme. For FCV washed best RI 79,45% and 63,40% of ARec presenting FE four times the enzyme Neutrase soluble when activated with glutaraldehyde. For CAB activated with epichlorohydrin, showed better RI 96,31% and 50,22% ARec. Supporters of QUIT- 2,5% activated glutaraldehyde showed better results of IR 75.44%, and 91.12% of ARec, SF five times greater than the soluble enzyme and evaluated their stability also operating with a drop of up to 41% after 10 cycles. For the enzyme L-arabinose isomerase were studied optimum conditions for activity of this enzyme in soluble form and develop protocol for immobilization support versatile and cheap as chitosanalginate epoxylated. Solutions of enzyme in buffer sodium acetate, sodium citrate and sodium phosphate, at pH ranging from 3,8 to 8,5 keeping under stirring at 25°C and 50°C. The best conditions for the activity of L-arabinose isomerase soluble presented with acetate buffer pH 5,5; citrate buffer pH 5,5; phosphate buffer pH 7,5 and 8,0. The derivatives were analyzed for yield of immobilization (Rl), activity recovered (ARec), half-life (t 1/1) and thermal stabilization factor at 75 °C (SF), compared with the soluble enzyme. In fixed at pH 8,0 showed higher Rl in 50 mM phosphate buffer after 24 hours, with 90,21% of ARec, at 25°C, tV2 of 44h at 75°C, 4.45% loss in activity during the stability study operating with 10 cycles and 1,83% loss of activity during 90 days of storage as compared to lower pH, in batch reactors. The results attract considerable interest due to a variety of possible applications, for example in the production proteins and peptides, for improving the texture and sensory properties of dairy products as well as isomerization on the synthesis and production of D-tagatose.